(untitled) (Journal of Scientific Research, 2023)
In this paper, the Bianchi type I cosmological models with perfect fluid is investigated in the framework of f(T) theory of gravitation. The functional form of the function f(T) such as f(T) = T + βT2 is used for investigation. The physical and kinematical properties of the models are obtained and analyzed. We obtained an accelerating and expanding universe.